University-Partnered New School Designs: Fertile Ground for Research–Practice Partnerships. (April 2017) - Quartz, Karen Hunter; Weinstein, Rhona S.; Kaufman, Gail; Levine, Harold; Mehan, Hugh; Pollock, Mica; Priselac, Jody Z.; Worrell, Frank C.
This commentary suggests that new school design is a fertile policy context for advancing research–practice partnerships. The authors represent four public universities that have created new school designs in partnership with urban school districts. Unlike the laboratory schools of previous generations, these university-partnered public schools were intentionally designed to disrupt persistent patterns of inequity and prepare low-income students of color to flourish in college. The authors argue that these schools provide a promising context for marrying research and practice to bring about fundamental change in schools, with potential for spread of innovation to districts and universities.